Using airborne laser scanning data in urban data management: set up of a flexible information system with open source components - Höfle, Bernhard; Rutzinger, Martin; Geist, Thomas; Stötter, Johann (2006)
In recent years airborne laser scanning has evolved into the state-of-the-art technology for topographic data acquisition. Applications for urban areas are recently growing to a greater extent (e.g. building extraction). Airborne laser scanning produces large datasets of point measurements, which demand for new strategies in data management. LISA (LIDAR Surface Analyses) is a concept for combining existing Open Source software for an efficient data management and analysis. The core components are the spatial database PostgreSQL/PostGIS, the geographical information system GRASS GIS and the statistical software R. Interfaces between the system components exist and therefore time-intensive data transfers are avoided. The open structure allows for developing workflows from simple applications to complex analysis. LISA is operationally used at the alpS - Centre for Natural Hazard Management. A large potential is given, for scientific applications as well as for operational tasks of public authorities
Aus: Proceedings of UDMS '06 : 25th Urban Data Management Symposium, Aalborg, Denmark, S. 7.11-7.24